Households' income and the cushioning effect of fiscal policy measures during the Great Lockdown - Vanda Almeida; Salvador Barrios Cobos; Michael Christl; Silvia De Poli; Alberto Tumino; Wouter Van Der Wielen (European Commission, Joint Research Centre (JRC), 2020)
We analyse the impact of the COVID-19 crisis on EU households' income and assess the cushioning effect of discretionary policy measures taken by the EU Member States. Our assessment is based on the European Commission Spring 2020 forecasts and counterfactual scenarios under a no policy change assumption. Our analysis suggests that over the course of 2020, on average, households' disposable income in the EU would fall by -5.9% due to the COVID-19 crisis without discretionary policy measures, and by -3.6% with policy intervention, pointing to a significant cushioning effect of these measures in protecting households against income losses. Furthermore, our results confirm that the impact of the COVID-19 crisis is likely to be highly regressive, with the poorest households being the most severely hit. However, discretionary policy measures are expected to contain the regressive effects of the recession, resulting in a quite homogeneous impact along the income distribution. Poverty, as measured by the at risk of poverty (AROP) rate, would increase significantly, even in presence of policy measures (+1.7pp), although this result depend on whether we anchor the poverty line to its pre-crisis level. When doing so, the impact of the COVID crisis on poverty becomes very close to the one observed in the aftermath of the financial crisis (i.e. +0.1pp) once policy measures are considered. Given the sheer size of the COVID shock, we might consider that the anchored poverty line may provide a more reliable assessment of the impact of the Great lockdown on poverty, however. Policy interventions are therefore seen as instrumental in cushioning against the impact of the crisis on inequality and poverty. Finally, our results suggest that the social impact of the Great Lockdown is likely to be much larger than the one experienced during the 2008/2009 financial crisis, at least for what concerns the immediate impact of the crisis.
Keywords: E24; D31; H12; H23; H84; 330; COVID-19; Great Lockdown; EUROMOD; household income; inequality; poverty